A blueprint paradox: Successful but unintended cross-national translation of total productive maintenance. Issue 4 (7th October 2014) - Rolfsen, Monica
Abstract : Purpose: – The purpose of this paper is to investigate if a manufacturing concept such as total productive maintenance (TPM) can be copied from one location to another. Design/methodology/approach: – Qualitative data were gathered from a single case. This includes interviews, participatory observation and document collection. Findings: – The authors present a company with an intention to make a pure copy from one location to another, and with identical technology, production equipment, owners, customers and products, the conditions for copying should thus be as sufficient as possible. However, several minor adjustments led to a translated version showing better results than the original. Research limitations/implications: – The paper provides a deep understanding of a unique case, but should be supplemented with more data in order to reach general conclusions. The main theoretical contribution is to develop an understanding of translation processes different from copying concepts by expanding models of change and transfer from a purely planned perspective to explaining success through the unplanned change of organizational vehicles better fit to the intended tools and techniques. Practical implications: – Many companies struggle with implementing total productive maintenance, and implementation and translation aspects are lacking in the literature. The paper provides an understanding on how TPM-practice was changed and adjusted when travelling from one location to another within the same company. Originality/value: – Few case studies on TPM and implementation have been described. The authors show in detail how minor adjustments led to wider changes, arguing that a pure copy is not possible. By including institutional theory focusing on translation, new insight on implementation of TPM is provided.